Adoption of written resolutions and without a meeting. The fit of the the Spanish legal order into a trend of comparative law that makes the processes of company will formation more flexible - Miranda Serrano, Luis María (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
There is a clear trend in comparative law in favor of admitting that in closed companies the resolutions may be adopted in writing and without a meeting (as is the case, for example, in German, British, Italian, Portuguese, Swiss or Argentine legislation). In 1953 the Spanish legislator moved in the same direction. However, since 1995 our corporate legislation has omitted express reference to this flexible mechanism for the formation of the company will. In spite of this, there are arguments to sustain that our law fits in with the aforementioned trend. This paper presents and analyzes these arguments, offering a study of the issue both from the perspective of current law (lege lata) and from a prospective point of view (lege ferenda).
Keywords: written resolutions and without a meeting; general meeting; universal meeting; meeting without session